Evaluation of oxidative stress in seminal plasma of adolescents with varicocele - Valéria Barradas; Mariana Pereira Antoniassi; Paula Intasqui; Marcilio Nichi; Ricardo Pimenta Bertolla; Deborah Montagnini Spaine (Bioscientifica, 2021)
Varicocele, defined by a dilation of efferent testicular veins, is the most commonly identifiable, surgically correctable lesion associated with male-factor infertility, starts at puberty and causes a progressive decline in fertility potential. The pathophysiology of infertility caused by this disease is still poorly understood, but it is suggested that the main mechanism is oxidative stress. Therefore, the aim of this study was to verify if the varicocele is associated with changes in enzymatic antioxidant mechanisms and seminal plasma lipid peroxidation levels in adolescents. We recruited 90 adolescents that were divided into control (C; n = 27); varicocele and normal semen (VNS; n =46); varicocele and altered semen (VAS; n =17). Seminal and serum levels of lipid peroxidation were quantified by thiobarbituric acid reactive substances (TBARS). Seminal plasma antioxidant profile was evaluated by the activities of catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD). The VAS group had increased lipid peroxidation levels when compared to the other groups. The levels of serum lipid peroxidation and activities of the enzymes SOD and GPx did not differ between groups. CAT was undetectable by the method used. In conclusion, in adolescents with varicocele and altered semen analysis, there is an increase in seminal lipid peroxidation levels compared to adolescents with varicocele and without seminal change and adolescents without evident varicocele. However, the observed oxidative stress is not caused by a decrease in superoxide dismutase and glutathione peroxidase activities, which did not differ between adolescents with and without evident varicocele.